ENVIRONMENTAL QUALITY AND OPTIMAL INVESTMENT IN TOURISM INFRASTRUCTURES: SETTING AN ENVIRONMENTALLY FRIENDLY PORT LOCATION COMBINED TO TOURIST DESTINATIONS USING TSP MODEL - Budiartha, Nyoman, R.M.; Manfaat, Djauhar; Achmadi, Tri (Bumi Lestari, 2010)
The rapid growth of cruise ships has encouraged the Indonesian government and Bali’s local governments in particular, to compete in developing and upgrading their existing ports. It needs a holistic and integrated transportation system before a decision to locate a port can be made. In order to avoid unconstructive local exploitation to the whole system and given the fact that cruises’ visits are usually only for a short period, requirement for a synergized system is fundamental, in order to measure the whole chain of factors and values involved in the decision making process. Traveling Salesman Problem (TSP) Model implemented in this study is expected to be able integrate tourist destinations and transportation system. Findings derived from this research will be used as guidance in managing many tourist destinations, which include the organization of local traffic and accessibility by introducing alternative routes; managing demands for transportation infrastructures, facilities, and services; reducing traffic congestion; controlling speed limit; mitigating air pollution; and synchronising location of the port and tourist destination. The strategic Environmental Sustainable Transportation is urgently needed to implement in Bali as the major tourist destination in Indonesia in order to minimized CO2 emission
Keywords: Port tourism; Environmental Sustainable Transportation; destinations; TSP model